Light-Activated Replication of Block Copolymer Fingerprint Patterns - Janes, Dustin W; Thode, Christopher J; Willson, C. Grant; Nealey, Paul F; Ellison, Christopher J (Macromolecules, 2013)
A strategy to replicate fingerprint patterns formed by the self-assembly of lamella-forming block copolymer (BCP) was investigated. To accomplish this, liquid conformal layers were placed between the surfaces of a “master” BCP film and a transparent “replica” substrate that solidified and covalently bonded to the BCP upon exposure to light. The benzophenone-containing conformal layer enabled pattern replication over areas limited only by the size of the samples and exposure field. The replication step is light activated, occurs below the glass transition of the BCP, and takes less than 1 h. This demonstration used a poly(styrene-b-methyl methacrylate) BCP with a bulk domain periodicity of 42 nm, but it is possible that the chemistry may be generalized to many other BCPs. Control experiments conducted with alternative conformal layer compositions indicate that interfacial photosensitization of the BCP by excited benzophenone, followed by propagation to residual acrylate groups present in the conformal layer, is the primary mechanism by which pattern replication takes place.